Resin composition for forming adhesive layer of semiconductor device
Patent Information
- Application Number
- JP2021002317
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-08
- Publication Date
- 2025-03-12
- Estimated Expiration
- 2041-01-08
AI Technical Summary
【0010】 本発明の樹脂組成物は、金属材料及びセラミック、並びに封止樹脂に対して、高温下でも高い密着性を有し、且つ、高温高湿環境への暴露試験後でも高い耐久力、即ち高い密着力の維持率を有する層を形成することができる。 すなわち、本発明によれば、高温下及び高温高湿環境暴露後でも、密着性に優れる半導体装置密着層、及び該半導体装置密着層形成用の樹脂組成物を提供することができる。 また、本発明によれば、高温下及び高温高湿環境下で動作する半導体装置でも、半導体装置を構成する各部材からの封止樹脂硬化物の剥離を防止できる、半導体密着層を有する 半導体装置、及びその製造方法を提供できる。
Smart Images

Figure 0007644406000023 
Figure 0007644406000001 
Figure 0007644406000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for forming an adhesive layer of a semiconductor device, an adhesive layer formed from the composition, and a method for manufacturing a semiconductor device using the composition. More specifically, the present invention relates to a resin composition for forming an adhesive layer of a semiconductor device, which contains a polyamic acid, an adhesive layer containing a polyimide resin obtained by imidizing the polyamic acid, and a method for manufacturing a semiconductor device using the composition. [Background technology]
[0002] Nowadays, semiconductor devices are used in various electronic devices, and are responsible for controlling the current and signals required for the operation of the devices. Semiconductor devices are generally constructed by stacking various components, such as semiconductor elements, bonding materials, metal electrodes, and insulating substrates. Since each of these components generally has a different thermal expansion coefficient, stress may be generated inside the element when heated or cooled, which may cause peeling between the components, especially from bonding materials such as solder. Such peeling between the components interferes with normal current control within the element, leading to malfunction of the element. In order to prevent this delamination between the components, the semiconductor element is mounted on a substrate or a lead frame, electrically connected, and then sealed with a sealing resin having a high elasticity, thereby protecting the semiconductor element from external chemical, electrical, and physical stimuli and restricting the thermal deformation of each layer stacked. In this case, preventing delamination caused by differences in the thermal expansion coefficient between the components constituting the semiconductor device and the sealing resin is also an important factor in preventing delamination between the above-mentioned components.
[0003] Meanwhile, in recent years, with the increasing voltage and frequency of controlled currents and signals, the development of semiconductor elements with wide band gaps, such as silicon carbide (SiC) and gallium nitride (GaN), is progressing as an alternative to conventional silicon semiconductors. Semiconductor devices incorporating such wide band gap semiconductor elements are designed to operate at higher temperatures than conventional devices, making the above-mentioned peeling problem even more prominent. To solve these problems, measures have been taken to add fillers to the encapsulating resin to lower the coefficient of thermal expansion (CTE) and reduce the difference in CTE between the encapsulating resin and surrounding materials. However, a large amount of filler must be added to sufficiently lower the CTE, which reduces the surface area of the resin component that is responsible for adhesion to the substrate surface, thereby essentially reducing adhesion to the base material. For this reason, it is difficult to ensure a certain level of adhesion.
[0004] In this situation, a method has been disclosed in which an intermediate layer made of polyimide resin, which is responsible for stress relaxation, is provided between members with different thermal expansion coefficients to improve adhesion (Patent Document 1).In addition, it has been reported that a polyimide resin obtained using a monomer having an amino group protected by a functional group that is released by heating can improve adhesion between a liquid crystal alignment film and a sealant by reacting with an epoxy compound or the like (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6168005 [Patent Document 2] International Publication No. 2017 / 164181 Summary of the Invention [Problem to be solved by the invention]
[0006] In a semiconductor device, if peeling occurs between components, insulation cannot be guaranteed, causing leakage currents and resulting in malfunctions, and external chemical or physical stimuli can damage the semiconductor chip. Therefore, in order to ensure the operational reliability of semiconductor devices, it is desirable that no delamination occurs between components even after undergoing thermal cycle testing (TCT), in which the temperature is repeatedly increased and decreased, power cycle testing (PCT), in which operation is repeatedly turned on and off, and exposure testing in high-temperature and high-humidity environments. However, the method described in Patent Document 1 is limited to evaluation of durability in thermal cycles, and does not disclose whether the polyimide resin described in Patent Document 1 exhibits operational reliability in high-temperature and high-humidity environments, making it difficult to predict. In addition, the method described in Patent Document 2 refers to the adhesion strength between a liquid crystal alignment film and a sealant in a liquid crystal device at room temperature, but does not disclose anything about adhesion to semiconductor peripheral members such as metal materials and ceramics (excluding glass).
[0007] Therefore, an object of the present invention is to provide a layer that exhibits high adhesion to metal materials, ceramics, and cured encapsulating resins at high temperatures and has durability even after exposure tests to high-temperature, high-humidity environments, i.e., a layer that has a high retention rate of adhesion, and a resin composition for forming such a layer for forming an adhesion layer in a semiconductor device. [Means for solving the problem]
[0008] As a result of intensive research aimed at solving the above problems, the inventors have found that an adhesion layer formed from a resin composition containing a polyamic acid having specific structural units obtained from a specific diamine component and a tetracarboxylic acid has high adhesion to metal materials, ceramics, and encapsulating resins, and has high durability even after exposure tests at high temperatures and in high-temperature and high-humidity environments, and is excellent as an adhesion layer for semiconductor devices, thereby completing the present invention.
[0009] That is, in a first aspect, the present invention relates to a resin composition for forming an adhesion layer for a semiconductor device, the resin composition comprising a polyamic acid obtained by reacting a diamine compound represented by the following formula (1), a diamine compound represented by the following formula (2), and a tetracarboxylic dianhydride, wherein the content of a structure derived from the diamine compound represented by formula (1) contained in the polyamic acid is 10 to 95 mol % in total, relative to a total of 100 mol % of the structures derived from the diamine compounds contained in the polyamic acid. [ka] (In the formula, A1 and A 2 each independently represents an organic acid group selected from the group consisting of a benzyloxycarbonyl group, a 9-fluorenylmethyloxycarbonyl group, an allyloxycarbonyl group, and a tert-butoxycarbonyl group; X represents a single bond or a divalent saturated hydrocarbon group having 1 to 20 carbon atoms, a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, or a divalent heterocycle; and Y represents a single bond, -O-, -CONH-, -NHCO-, -OCO-, -COO-, -NH-CO―NH-, -NHCOO-, or -OCONH-. [ka] (In the formula, m is an integer of 1 to 4.) As the second viewpoint, A 1 and A 2 is a tert-butoxycarbonyl group. As a third aspect, the present invention relates to the resin composition for forming an adhesion layer for a semiconductor device according to the first aspect or the second aspect, in which Y is -CONH-. As a fourth aspect, the present invention relates to the resin composition for forming an adhesion layer for a semiconductor device according to any one of the first to third aspects, in which X is a divalent saturated hydrocarbon group having 1 to 18 carbon atoms, a divalent unsaturated hydrocarbon group having 2 to 18 carbon atoms, a divalent aromatic hydrocarbon group having 6 to 18 carbon atoms, or a divalent heterocycle. As a fifth aspect, the present invention relates to the resin composition for forming an adhesion layer for a semiconductor device according to any one of the first to fourth aspects, in which the diamine compound represented by formula (1) is a diamine compound represented by the following formula (3): [ka] As a sixth aspect, the present invention relates to a resin composition for forming an adhesion layer for a semiconductor device according to any one of the first to fifth aspects, in which the diamine compound represented by formula (2) is at least one diamine compound selected from the group consisting of diamine compounds represented by the following formulas (2a) to (2d): [ka] As a seventh aspect, the present invention relates to the resin composition for forming an adhesion layer for a semiconductor device according to any one of the first to sixth aspects, in which the tetracarboxylic dianhydride is a tetracarboxylic dianhydride represented by the following formula (4): [ka] (In the formula, Z represents a tetravalent organic group having 6 to 13 carbon atoms and an aromatic hydrocarbon group.) According to an eighth aspect, the present invention relates to the resin composition for forming an adhesion layer for a semiconductor device according to the seventh aspect, in which Z is selected from the group consisting of tetravalent organic groups having structures represented by the following formulas (5a) to (5k): [ka] (In the formula, * represents a bond.) As a ninth aspect, the present invention relates to an adhesion layer for a semiconductor device, which is a cured product of the resin composition for forming an adhesion layer for a semiconductor device according to any one of the first to eighth aspects. According to a tenth aspect, the present invention relates to the semiconductor device adhesion layer according to the ninth aspect, in which an imidization rate of the polyamic acid is 80% to 100%. As an eleventh aspect, the present invention relates to the adhesion layer of a semiconductor device according to the ninth or tenth aspect, characterized in that when a metal material, ceramic or cured sealing resin provided with the adhesion layer is heated at 175°C for 6 hours and then measured at 175°C, an adhesion force A between the adhesion layer and the metal material, ceramic or cured sealing resin is 15 MPa or more, and when a metal material, ceramic or cured sealing resin provided with the adhesion layer is exposed under conditions of 85°C and 85% RH for 168 hours and then measured at 175°C, an adhesion force B between the adhesion layer and the metal material, ceramic or cured sealing resin is 70% or more of the adhesion force A. A twelfth aspect relates to a semiconductor device having the semiconductor device adhesion layer according to any one of the ninth to eleventh aspects. As a thirteenth aspect, the present invention relates to a method for manufacturing a semiconductor device, the method including: applying the resin composition for forming an adhesion layer of a semiconductor device according to any one of the first to eighth aspects to at least a part of a semiconductor element, a substrate carrying the semiconductor element, and / or a lead electrode joined to the semiconductor element to obtain a coating film; and heating the coating film to form an adhesion layer. As a fourteenth aspect, the present invention relates to a method for producing a semiconductor device according to the thirteenth aspect, further comprising the step of forming a cured encapsulating resin on the adhesion layer after the adhesion layer is formed. Effect of the Invention
[0010] The resin composition of the present invention has high adhesion to metal materials, ceramics, and sealing resins even at high temperatures, and can form a layer that has high durability, i.e., high adhesion retention, even after exposure tests in high-temperature and high-humidity environments. That is, according to the present invention, it is possible to provide an adhesion layer for a semiconductor device, which has excellent adhesion even at high temperatures and after exposure to a high-temperature and high-humidity environment, and a resin composition for forming the adhesion layer for a semiconductor device. In addition, according to the present invention, a semiconductor device having a semiconductor adhesion layer can be provided, which can prevent peeling of the cured sealing resin from each member constituting the semiconductor device even when the semiconductor device is operated under high temperature and high temperature and high humidity environments. A semiconductor device and a manufacturing method thereof can be provided. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a schematic diagram of a semiconductor device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Resin composition> The resin composition of the present invention is a resin composition used for forming an adhesion layer (i.e., a primer layer for a semiconductor encapsulant (cured encapsulating resin)) in at least a part of the interface between a cured encapsulating resin and a substrate and / or a lead electrode in a semiconductor device, i.e., at least a part between the cured encapsulating resin and the substrate and / or at least a part between the cured encapsulating resin and the lead electrode, the resin composition comprising a polyamic acid obtained by reacting a diamine compound represented by the following formula (1), a diamine compound represented by the following formula (2), and a tetracarboxylic dianhydride compound, and the content of the structure derived from the diamine compound represented by formula (1) contained in the polyamic acid is 10 to 95 mol % in total, relative to a total of 100 mol % of the structures derived from the diamine compounds contained in the polyamic acid.
[0013] [Diamine compound represented by formula (1)] [ka] In formula (1), A 1 and A 2 are each independently an organic acid group (protecting group) that can be removed by heating at 150° C. or higher, and are preferably an organic acid group selected from the group consisting of a benzyloxycarbonyl group, a 9-fluorenylmethyloxycarbonyl group, an allyloxycarbonyl group, and a tert-butoxycarbonyl group, and are more preferably a tert-butoxycarbonyl group. In the diamine compound represented by formula (1), A 1 Or A 2 The amino group protected by A has low reactivity, but when heated to 150 degrees or higher, 1 and A 2 is eliminated to become an amino group. For example, A 1 The amino group protected by A is converted by heating. 1 is eliminated and can then react with an ortho -NHC(O)- moiety to form a heterocycle.
[0014] In formula (1), Y represents a single bond, -O-, -CONH-, -NHCO-, -OCO-, -COO-, -NH-CO-NH-, -NHCOO- or -OCONH-, preferably -CONH-.
[0015] In formula (1), X represents a single bond, a divalent saturated hydrocarbon group having 1 to 20 carbon atoms, a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, an aromatic hydrocarbon group, or a divalent heterocycle.
[0016] Examples of the divalent saturated hydrocarbon group having 1 to 20 carbon atoms include linear or branched alkylene groups, such as a methylene group, an ethylene group, an n-propylene group, an isopropylene group, n-butylene group, s-butylene group, n-pentylene group, 1-methylbutylene group, 2-methylbutylene group, 3-methylbutylene group, n-pentylene group, 1,1-dimethylpropylene group, 1,2-dimethylpropylene group, 2,2-dimethylpropylene group, 1,3-dimethylpropylene group, n-hexylene group, 1-methylheptylene group, 2-methylheptylene group, 3-methylheptylene group, 1,1-dimethylbutylene group, 1,2-dimethylbutylene group, 1,3-dimethylbutylene group, 2,2-dimethylbutylene group Examples of the alkylene group include an alkylene group having 1 to 18 carbon atoms, a 2,3-dimethylbutylene group, a 3,3-dimethylbutan-2-ylene group, a 2,3-dimethylbutan-2-ylene group, a 3-hexylene group, a 2-ethylpentylene group, a 2-methylpentan-3-ylene group, a heptylene group, an octylene group, a nonylene group, a decylene group, an undecylene group, a dodecylene group, a tridecylene group, a tetradecylene group, a pentadecylene group, a hexadecylene group, a heptadecylene group, an octadecylene group, a nonadecylene group, and an icosylene group. In the present invention, an alkylene group having 1 to 18 carbon atoms is preferred, and an alkylene group having 1 to 6 carbon atoms is more preferred.
[0017] Examples of the divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms include ethenylene, propenylene, butenylene, pentenylene, hexenylene, heptenylene, octenylene, nonenylene, decenylene, undecenylene, dodecenylene, tridecenylene, tetradecenylene, pentadecenylene, hexadecenylene, heptadecenylene, octadecenylene, nonadecenylene and eicosenylene. In the present invention, unsaturated hydrocarbon groups having 2 to 18 carbon atoms are preferred.
[0018] Examples of divalent aromatic hydrocarbon groups having 6 to 20 carbon atoms include a phenylene group, a naphthylene group, an anthracenylene group, a phenanthrenylene group, etc. In the present invention, unsaturated hydrocarbon groups having 6 to 18 carbon atoms are preferred.
[0019] Examples of divalent heterocycles include groups in which two hydrogen atoms have been removed from quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, and benzoxazole.
[0020] A diamine compound represented by the following formula (3) is preferred. [ka]
[0021] The diamine compounds represented by formula (1) may be used alone or in combination of two or more kinds.
[0022] [Diamine compound represented by formula (2)] One of the raw materials for the polyamic acid used in the present invention is a diamine compound represented by the following formula (2). [ka] In formula (2), m is an integer of 1 to 4. Preferably, the diamine compound is at least one selected from the group consisting of diamine compounds represented by the following formulas (2a) to (2d). [ka] The diamine compounds represented by formula (2) can be used alone or in combination of two or more kinds.
[0023] [Tetracarboxylic acid dianhydride] The tetracarboxylic dianhydride may be any one having two dicarboxylic anhydride moieties in the molecule, and commercially available or known dicarboxylic anhydrides can be used. Specific examples of carboxylic acids include 1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-tetramethyl-1,2,3,4-cyclobutane tetracarboxylic dianhydride, 1,2,3,4-cyclopentane tetracarboxylic dianhydride, 2,3,4,5-tetrahydrofuran tetracarboxylic dianhydride, 1,2,4,5-cyclohexane tetracarboxylic dianhydride, 3,4- Dicarboxy-1-cyclohexylsuccinic dianhydride, 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalenesuccinic dianhydride, 1,2,3,4-butanetetracarboxylic dianhydride, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic dianhydride, 3,3',4,4'-dicyclohexyltetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, cis-3,7-dibutylcycloocta-1,5-diene-1,2,5,6-tetracarboxylic dianhydride, tricyclo[4.2.1.0 2,5 ]nonane-3,4,7,8-tetracarboxylic acid-3,4:7,8-dianhydride, hexacyclo[6.6.0.1 2,7 .0 3,6 .1 9,14 .0 10,13]Hexadecane-4,5,11,12-tetracarboxylic acid-4,5:11,12-dianhydride, 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid anhydride, pyromellitic dianhydride, benzene-1,2,3,4-tetracarboxylic acid dianhydride, naphthalene-1,2,3,4-tetracarboxylic acid dianhydride, naphthalene-1,2,5,6-tetracarboxylic acid dianhydride, naphthalene-1,2,6,7-tetracarboxylic acid dianhydride, naphthalene-1,2,7,8-tetracarboxylic acid dianhydride tetracarboxylic dianhydride, naphthalene-2,3,5,6-tetracarboxylic dianhydride, naphthalene-2,3,6,7-tetracarboxylic dianhydride, naphthalene-1,4,5,8-tetracarboxylic dianhydride, biphenyl-2,2',3,3'-tetracarboxylic dianhydride, biphenyl-2,3,3',4'-tetracarboxylic dianhydride, biphenyl-3,3',4,4'-tetracarboxylic dianhydride, anthracene-1,2,3,4-tetracarboxylic dianhydride, anthracene-1,2,5,6-tetracarboxylic dianhydride, anthracene 1,2,6,7-tetracarboxylic dianhydride, anthracene-1,2,7,8-tetracarboxylic dianhydride, anthracene-2,3,6,7-tetracarboxylic dianhydride, phenanthrene-1,2,3,4-tetracarboxylic dianhydride, phenanthrene-1,2,5,6-tetracarboxylic dianhydride, phenanthrene-1,2,6,7-tetracarboxylic dianhydride, phenanthrene-1,2,7,8-tetracarboxylic dianhydride, phenanthrene Examples of the dianhydride include, but are not limited to, phenanthrene-1,2,9,10-tetracarboxylic dianhydride, phenanthrene-2,3,5,6-tetracarboxylic dianhydride, phenanthrene-2,3,6,7-tetracarboxylic dianhydride, phenanthrene-2,3,9,10-tetracarboxylic dianhydride, phenanthrene-3,4,5,6-tetracarboxylic dianhydride, and phenanthrene-3,4,9,10-tetracarboxylic dianhydride. These may be used alone or in combination of two or more.
[0024] Among them, from the viewpoint of improving the adhesion of the obtained film and the maintenance rate of the adhesion after exposure to a high-temperature and high-humidity environment, aromatic carboxylic acid dianhydrides having one or more benzene nuclei are preferred. For example, tetracarboxylic acid dianhydrides represented by the following formula (4) can be mentioned. [ka] In formula (4), Z represents a tetravalent organic group having 6 to 13 carbon atoms and an aromatic hydrocarbon group. Preferably, Z represents a tetravalent organic group having 6 to 13 carbon atoms and one or two benzene nuclei. Specific examples of Z include, but are not limited to, structures represented by the following formulas (5a) to (5k), and preferably, structures represented by the formulas (5a), (5g), and (5i). [ka] In the formulas (5a) to (5k), * represents a bond. The tetracarboxylic dianhydrides can be used alone or in combination of two or more kinds.
[0025] [Polyamic acid] The polyamic acid used in the present invention can be produced by reacting a mixture of the diamine compound represented by the above formula (1) and the diamine compound represented by the above formula (2) with a tetracarboxylic dianhydride. The mixture of the diamine compounds and the tetracarboxylic dianhydride can be mixed and reacted in a state where each is dissolved or dispersed in a solvent.
[0026] The mixture of diamine compounds may contain diamine compounds other than the diamine compounds represented by formula (1) or formula (2) as long as the desired effects are not impaired. In the present invention, the amount of the diamine compound represented by formula (1) contained in the mixture of diamine compounds is 10 to 95 mol %, preferably 10 to 50 mol %, and more preferably 10 to 30 mol %. Thus, in the polyamic acid of the present invention, the content of the structure derived from the diamine compound represented by formula (1) is 10 to 95 mol %, preferably 10 to 50 mol %, and more preferably 10 to 30 mol %, relative to a total of 100 mol % of the structures derived from the diamine compounds contained in the polyamic acid. If the structure derived from the diamine compound represented by formula (1) exceeds this range, gas components generated by the elimination reaction may generate bubbles in the film, which may reduce the adhesion to metal materials, ceramics, and cured sealing resins.
[0027] When the tetracarboxylic dianhydride represented by formula (4) is used, the amount of the tetracarboxylic dianhydride used in the reaction is preferably 70 mol % or more, more preferably 80 mol % or more, even more preferably 90 mol % or more, still more preferably 95 mol % or more, and most preferably 100 mol %. By adopting such an amount, it is possible to obtain an adhesive layer that has excellent adhesion to metal materials and ceramics, as well as to the cured product of the encapsulating resin, and has high durability against exposure to high temperature and high humidity conditions.
[0028] The charging ratio of the diamine component and the tetracarboxylic dianhydride component cannot be generally defined because it is appropriately determined in consideration of the target molecular weight and molecular weight distribution, the type of diamine, the type of tetracarboxylic dianhydride, and the like; however, it is about 0.7 to 1.3, preferably about 0.8 to 1.2, and more preferably about 0.9 to 1.1, of the diamine component per 1 of the tetracarboxylic dianhydride component.
[0029] The organic solvent used in the synthesis of polyamic acid is not particularly limited as long as it does not adversely affect the reaction, and specific examples thereof include m-cresol, N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N-methylcaprolactam, dimethylsulfoxide (DMSO), tetramethylurea, pyridine, dimethylsulfone, hexamethylphosphoric triamide (HMPA), and γ-butyrolactone. These may be used alone or in combination. Furthermore, even if a solvent does not dissolve polyamic acid, it may be added to the above solvent within a range in which a uniform solution can be obtained. The organic solvents may be used alone or in combination of two or more kinds.
[0030] The reaction temperature may be any temperature at which the reaction can proceed without imidizing the resulting polyamic acid to form a polyimide, and may be any temperature selected from, for example, -20°C to 100°C, -20°C to 50°C, or 0°C to 30°C, such as room temperature (23°C). However, the resin composition of the present invention may contain a polyamic acid in which amic acid moieties are partially imidized, so long as the resin composition can be uniformly applied to the substrate and electrodes and the desired effects are not impaired.
[0031] The reaction time cannot be generally defined since it depends on the reaction temperature and the reactivity of the raw materials, but it is usually about 1 to 100 hours.
[0032] The weight-average molecular weight of the polyamic acid thus obtained is usually about 5,000 to 500,000, but from the viewpoint of improving the function of the obtained film as an adhesive layer, it is preferably about 10,000 to 300,000, more preferably about 50,000 to 250,000. Note that in the present invention, the weight-average molecular weight is a polystyrene-equivalent value measured by gel permeation chromatography (GPC).
[0033] The polyamic acid obtained by the reaction can be used as a resin composition as it is or after dilution or concentration. Alternatively, a poor solvent such as methanol, ethanol, or isopropyl alcohol may be added to the polyamic acid-containing solution to precipitate and isolate the polyamic acid, and the isolated polyamic acid may be redissolved in a suitable solvent to obtain a polyamic acid-containing solution, which may then be used as the resin composition of the present invention. The solvent for diluting the polyamic acid and the solvent for redissolving the isolated polyamic acid are not particularly limited as long as they dissolve the obtained polyamic acid, and various solvents listed in [Solvent] described later can be used. Even if a solvent does not dissolve the polyamic acid by itself, it may be added to the above-mentioned solvents as long as the polyamic acid does not precipitate.
[0034] [solvent] The solvent used in the resin composition of the present invention is not particularly limited as long as it dissolves the polyamic acid and can also dissolve or disperse other optional components such as the epoxy resin described below. Examples of the solvent include aliphatic hydrocarbons such as heptane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate, propyl acetate, butyl acetate, and γ-butyrolactone (GBL); methyl hydroxyacetate, ethyl hydroxyacetate, propyl hydroxyacetate, methyl lactate, ethyl lactate, propyl lactate, methyl 3-hydroxypropionate, ethyl 3-hydroxypropionate, propyl 3-hydroxypropionate, methyl 2-hydroxy-2-methylpropionate, ethyl ... -Hydroxy esters such as methyl hydroxy-3-methylbutanoate; methyl methoxyacetate, ethyl methoxyacetate, propyl methoxyacetate, methyl ethoxyacetate, ethyl ethoxyacetate, propyl ethoxyacetate, methyl propoxyacetate, ethyl propoxyacetate, propyl propoxyacetate, methyl 2-methoxypropionate, ethyl 2-methoxypropionate, propyl 2-methoxypropionate, methyl 2-ethoxypropionate, ethyl 2-ethoxypropionate, propyl 2-ethoxypropionate, methyl 3-methoxypropionate, 3-methoxy Ethyl propionate, Propyl 3-methoxypropionate, Methyl 3-ethoxypropionate, Ethyl 3-ethoxypropionate, Propyl 3-ethoxypropionate, Methyl 3-propoxypropionate, Ethyl 3-propoxypropionate, Propyl 3-propoxypropionate, Methyl cellosolve acetate, Ethyl cellosolve acetate, Butyl cellosolve acetate, Propylene glycol monomethyl ether acetate (PGMEA), Propylene glycol monoethyl ether acetate, Propylene glycol monopropyl ether acetate Ether esters such as acetate, propylene glycol monomethyl ether propionate, propylene glycol monoethyl ether propionate, and propylene glycol monopropyl ether propionate; amides such as N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methyl-2-pyrrolidone (NMP); ketones such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), 4-hydroxy-4-methyl-2-pentanone, cyclopentanone (CPN), and cyclohexanone;Alcohols such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ether, propylene glycol monopropyl ether, and propylene glycol monobutyl ether; ethers such as tetrahydrofuran (THF), diethylene glycol dimethyl ether, diethylene glycol diethyl ether, and diethylene glycol ethyl methyl ether, and mixtures thereof;
[0035] Among these, solvents with normal boiling points (boiling points at 1 atmospheric pressure) of 150°C or less are This is preferable because it has the advantage that the solvent can be removed at the same time as the imidization of the polyamic acid described below. The lower limit of the standard boiling point of the solvent is not particularly limited, but it can be set to, for example, 70° C. or higher in consideration of storage of the resin composition and handling of the resin composition on a substrate, etc. Examples of such a solvent include the solvents used in the synthesis of the above-mentioned amic acid, and preferably N-methyl-2-pyrrolidone, but is not limited thereto.
[0036] [Epoxy resin] The resin composition of the present invention may contain an epoxy resin within a range that does not impair the intended effects. The epoxy resin contained in the resin composition generally refers to an epoxy compound having at least two epoxy groups in the molecule, and in the present invention, there is no particular limitation, and various epoxy resins, including commercially available products, can be used.
[0037] Examples of such epoxy resins include 1,2,7,8-diepoxyoctane, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, 1,6-dimethylolperfluorohexane diglycidyl ether, (poly)ethylene glycol diglycidyl ether, (poly)propylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, trimethylolethane tri ... glycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, 2,6-diglycidylphenyl glycidyl ether, resorcinol diglycidyl ether, bis(2,7-diglycidyloxynaphthalene-1-yl)methane, 1,1,2,2-tetrakis(4-glycidyloxyphenyl)ethane, 1,1,3-tris( 4-glycidyloxyphenyl)propane, bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, bisphenol S diglycidyl ether, tetrabromobisphenol A diglycidyl ether, hydrogenated bisphenol A diglycidyl ether, bisphenol hexafluoroacetone diglycidyl ether, bis(2,3-epoxycyclopentyl)ether, 1,2-bis(3,4-epoxycyclohexylmethoxy)ethane, ethylene glycol bis(3,4-epoxycyclohexanecarboxylate), 3,4- (3,4-epoxycyclohexyl)methyl epoxycyclohexanecarboxylate, 4,5-epoxy-2-methylcyclohexylmethyl 4,5-epoxy-2-methylcyclohexanecarboxylate, bis(3,4-epoxycyclohexylmethyl) adipate, 1,2-epoxy-4-(epoxyethyl)cyclohexane, 4-(spiro[3,4-epoxycyclohexane-1,5'-[1,3]dioxane]-2'-yl)-1,2-epoxycyclohexane, diglycidyl adipate, diglycidyl phthalate, diglycidyl tetrahydrophthalate, 1,Diglycidyl 2-cyclohexanedicarboxylate, triglycidyl isocyanurate, tris(3,4-epoxybutyl)isocyanurate, tris(4,5-epoxypentyl)isocyanurate, tris(5,6-epoxyhexyl)isocyanurate, tris(6,7-epoxyheptyl)isocyanurate, tris(7,8-epoxyoctyl)isocyanurate, tris(8,9-epoxynonyl)isocyanurate, tris(2-glycidyloxyethyl)isocyanurate, monoa N,N'-diglycidyl N''-(2,3-dipropionyloxypropyl)isocyanurate, N,N'-bis(2,3-dipropionyloxypropyl)N''-glycidyl isocyanurate, 1,3,5-tris(2-(2,2-bis(glycidyloxymethyl)butoxycarbonyl)ethyl)isocyanurate, tris(2,2-bis(glycidyloxymethyl)butyl)3,3',3''-(2,4,6-trioxo-1,3,5-triazine-, 1,3,5-triyl) tripropanoate, N,N-diglycidyl-4-glycidyloxyaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 4,4'-methylenebis(N,N-diglycidylaniline), 2-(4,4-dimethylpentan-2-yl)-5,7,7-trimethyloctyl glycidyl ether, 2-(4,4-dimethylpentan-2-yl)-5,7,7-trimethyloctanoic acid glycidyl, 2-(4,4-dimethylpentan-2-yl)-5,7,7-trimethyloctanoic acid glycidyl, 2-(4,4-dimethylpentan- Examples of epoxy resins that can be used include, but are not limited to, 2,2-bis(glycidyloxymethyl)butyl (2-yl)-5,7,7-trimethyloctanoate, phenol novolac type epoxy resins, cresol novolac type epoxy resins, naphthalene novolac type epoxy resins, anthracene novolac type epoxy resins, biphenylene novolac type epoxy resins, xylylene novolac type epoxy resins, triphenolmethane novolac type epoxy resins, tetrakisphenol novolac type epoxy resins, dicyclopentadiene novolac type epoxy resins, and the like. In addition, the epoxy resin may be a commercially available product, such as TEPIC (registered trademark)-G, TEPIC-S, TEPIC-SS, TEPIC-SP, TEPIC-L, TEPIC-HP, TEPIC-VL, TEPIC-FL, TEPIC-PAS B22, TEPIC-PAS B26, TEPIC-PAS B27, TEPIC-PAS B29, TEPIC-PAS B28, TEPIC-PAS B29 ... Examples of such resins include B26L, UC, FOLDI (registered trademark)-E101, and E201 (all manufactured by Nissan Chemical Industries, Ltd.), jER (registered trademark) 828, 807, YX8000, and 157S70 (all manufactured by Mitsubishi Chemical Corporation), Rikaresin (registered trademark) DME100 (manufactured by New Japan Chemical Co., Ltd.), Celloxide 2021P (manufactured by Daicel Corporation), EPICLON (registered trademark) HP-4700, HP-4710, and HP-7200L (all manufactured by DIC Corporation), and AV Light (registered trademark) TEP-G (manufactured by Asahi Organic Chemicals Co., Ltd.). These epoxy resins may be used alone or in combination.
[0038] When the resin composition of the present invention contains an epoxy resin, the amount of the epoxy resin may be 1 to 30 parts by mass, for example 5 to 20 parts by mass, per 100 parts by mass of the polyamic acid.
[0039] [Other ingredients] The resin composition of the present invention may also contain conventional additives as necessary. Examples of such additives include surfactants, adhesion promoters, thickeners, sensitizers, defoamers, leveling agents, coating improvers, lubricants, stabilizers (antioxidants, heat stabilizers, light resistance stabilizers, etc.), plasticizers, dissolution promoters, fillers (silica, etc.), antistatic agents, etc. These additives may be used alone or in combination of two or more.
[0040] A surfactant may be added to the resin composition of the present invention in order to improve the coating property. Examples of such surfactants include fluorine-based surfactants, silicone-based surfactants, nonionic surfactants, etc., but are not limited thereto. The surfactants may be used alone or in combination of two or more kinds. Among these surfactants, fluorine-based surfactants are preferred because of their high effect of improving coatability. Specific examples of fluorine-based surfactants include, but are not limited to, F-TOP (registered trademark) EF-301, EF-303, and EF-352 [all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.], Megafac (registered trademark) F-171, F-173, F-482, R-08, R-30, R-90, and BL-20 [all manufactured by DIC Corporation], Fluorad FC-430 and FC-431 [all manufactured by 3M Japan Ltd.], Asahiguard (registered trademark) AG-710 [manufactured by Asahi Glass Co., Ltd.], Surflon S-382, SC-101, SC-102, SC-103, SC-104, SC-105, and SC-106 [all manufactured by AGC Seimi Chemical Co., Ltd.], and the like. When the resin composition of the present invention contains a surfactant, the amount of the surfactant added is 0.01 to 5 mass %, preferably 0.01 to 3 mass %, and more preferably 0.01 to 2 mass %, based on the solid content of the resin composition.
[0041] In the resin composition of the present invention, inorganic fine particles such as silica may be added in order to improve the flatness of the coating film. As such inorganic fine particles, commercially available products can be suitably used, for example, Snowtex (registered trademark) series, Organosilicasol series (both manufactured by Nissan Chemical Industries, Ltd.), etc. The inorganic fine particles can be used alone or in combination of two or more kinds. When the resin composition of the present invention contains inorganic fine particles, the blending amount thereof is 0.1 to 20 mass %, preferably 0.1 to 10 mass %, more preferably 1 to 10 mass %, based on the solid content of the resin composition.
[0042] The resin composition of the present invention may further contain an adhesion promoter for the purpose of improving adhesion to the encapsulating resin cured product, the substrate and / or the lead electrode. Examples of these adhesion promoters include chlorosilanes such as chlorotrimethylsilane, trichloro(vinyl)silane, chloro(dimethyl)(vinyl)silane, chloro(methyl)(diphenyl)silane, and chloro(chloromethyl)(dimethyl)silane; methoxytrimethylsilane, dimethoxydimethylsilane, diethoxydimethylsilane, ethoxy(dimethyl)(vinyl)silane, dimethoxydiphenylsilane, triethoxy(phenyl)silane, 3-chloropropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-glycidyloxypropyltrimethoxysilane, trimethoxysilane, tetra ... Examples of the adhesion promoter include alkoxysilanes such as trimethoxy(3-(N-piperidinyl)propyl)silane; silazanes such as hexamethyldisilazane, N,N'-bis(trimethylsilyl)urea, dimethyl(trimethylsilyl)amine, and trimethylsilylimidazole; nitrogen-containing heterocyclic compounds such as imidazole, indazole, benzimidazole, benzotriazole, mercaptoimidazole, mercaptopyrimidine, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, 2-mercaptobenzothiazole, urazole, and thiouracil; and ureas or thioureas such as 1,1-dimethylurea and 1,3-dimethylurea. These adhesion promoters can be used alone or in combination of two or more. When the resin composition of the present invention contains an adhesion promoter, the amount of the adhesion promoter is usually 20 mass % or less, preferably 0.01 to 10 mass %, and more preferably 0.05 to 5 mass %, based on the solid content of the resin composition.
[0043] [Method for preparing resin composition] The resin composition of the present invention can be obtained by mixing a polyamic acid obtained by reacting a diamine compound represented by the above formula (1), a diamine compound represented by the above formula (2), and a tetracarboxylic dianhydride, and, if necessary, a solvent and other components. The mixing method is not particularly limited as long as it can achieve uniform mixing, and can be carried out, for example, using a reaction flask and a stirring blade or a mixer. The mixing is carried out under heating as necessary in consideration of the viscosity, at a temperature of 10 to 100°C for 0.5 to 1 hour.
[0044] The solid content concentration in the resin composition of the present invention can be, for example, 0.1 to 100 mass%, or 1 to 80 mass%, or 10 to 80 mass%, or 10 to 60 mass%, etc. Here, the solid content refers to all components other than the solvent in the resin composition, and even liquid components are included in the solid content. The resin composition of the present invention can be adjusted to any viscosity, and has a suitable viscosity for use as a resin composition for forming an adhesive layer for a semiconductor device. For example, when the objective is to reproducibly obtain a film having a thickness of about 0.1 to 30 μm as described below, the viscosity is usually about 500 to 50,000 mPa·s at 25° C., and preferably about 1,000 to 20,000 mPa·s. The solid content and viscosity of the resin composition of the present invention are determined in consideration of the film-forming efficiency and the surface uniformity of the coating film. Please select appropriately.
[0045] <Semiconductor device> The semiconductor device of the present invention is a semiconductor device comprising a semiconductor element, a substrate on which the semiconductor element is mounted and / or a lead electrode joined to the semiconductor element, and a cured encapsulating resin that encapsulates them, and has an adhesion layer made of an imidized product of the above-mentioned resin composition at least in a portion between the cured encapsulating resin and the substrate and / or the lead electrode, i.e., at least in a portion between the cured encapsulating resin and the substrate and / or at least in a portion of the contact portion between the cured encapsulating resin and the lead electrode.
[0046] The semiconductor device of the present invention can be obtained by a manufacturing method including a step of applying the resin composition of the present invention to at least a part of a substrate carrying a semiconductor element and / or a lead electrode bonded to the semiconductor element to obtain a coating film, and a step of imidizing the coating film of the applied resin composition to form an adhesive layer. The manufacturing method of the semiconductor device can further include a step of forming a cured encapsulating resin on the adhesive layer after forming the adhesive layer. For example, an example of a semiconductor device 1 and a manufacturing method thereof will be described with reference to FIG. 1, but the present invention is not limited thereto. The semiconductor device 1 comprises a semiconductor element 3, a ceramic substrate 6 formed by contacting a copper substrate, a lead frame 7 including a lead electrode joined to the semiconductor element 3 via a bonding wire 8, and a cured encapsulating resin 2 that encapsulates these, and has a semiconductor device adhesion layer 9 formed from the above resin composition between the cured encapsulating resin 2 and the copper substrate 5, the ceramic substrate 6, the bonding wire 8, and the lead frame 7. The method for producing the semiconductor device 1 includes the steps of: mounting a semiconductor element 3 using solder 4 on a substrate on which a semiconductor element is mounted, the substrate being a copper substrate 5 in contact with a ceramic substrate 6; and wire-bonding the semiconductor element 3 to a lead frame 7 including a lead electrode using a bonding wire; and applying the above-mentioned resin composition to at least a portion of the substrate (copper substrate 5 and ceramic substrate 6) on which the semiconductor element 3 is mounted and the lead frame 7 bonded to the semiconductor element 3 via a bonding wire 8 to obtain a coating film; and imidizing the coating film of the applied resin composition to form a semiconductor device adhesion layer 9. The method for producing the semiconductor device 1 may further include the step of forming an encapsulating resin cured product 2 on the adhesion layer 9 after the semiconductor adhesion layer 9 is formed.
[0047] As the substrate on which the semiconductor element is mounted and the lead electrodes joined to the semiconductor element, known substrates and lead electrodes can be used. Examples of metal materials used for the substrate or electrode include chromium, tungsten, molybdenum, manganese, copper, silver, palladium, gold, platinum, nickel, cobalt, and alloys thereof, and preferably copper, nickel, silver, and alloys of two or more of these. Metal oxides such as silver oxide, copper oxide, palladium oxide, and tin oxide can also be used. The ceramics used for the substrate include ceramics other than glass, such as aluminum nitride, silicon nitride, boron nitride, and aluminum oxide (alumina).
[0048] In the step of applying the resin composition according to the present invention to at least a portion of a substrate carrying a semiconductor element and / or a lead electrode bonded to a semiconductor element, the method of applying the resin composition is not particularly limited, and examples thereof include flow coating, spin coating, spray coating, screen printing, flexographic printing, inkjet printing, casting, bar coating, curtain coating, roll coating, gravure coating, dipping, slitting, and dispensing. The resin composition of the present invention may be applied to the entire surface of the substrate, or to the entire surface or a part of the substrate and / or lead electrode that is in contact with the cured encapsulating resin. It is preferable to coat the entire surface of the substrate and / or lead electrode that comes into contact with the substrate.
[0049] In the step of imidizing the applied coating film of the resin composition to form an adhesive layer, the method of imidizing the coating film of the resin composition is not particularly limited. The conditions for imidizing the coating film include the following: 1 and A 2The temperature and time conditions may be such that the diamine and the acid dianhydride end are dehydrated and cyclicly closed to form an imide bond, for example, at 100 to 350° C. or 150 to 250° C., and usually for about 30 minutes to 3 hours, for example, for about 30 minutes to 2 hours. By using the above temperature and time conditions, the polyamic acid can be imidized to a polyimide at the same time as the solvent is removed. The imidization rate of the adhesive layer in the present invention is 50% or more, preferably 80% or more, more preferably 95% or more, and even more preferably 100%. Examples of the equipment used for the imidization include a hot plate, an oven, etc. The imidization may be performed in an atmosphere of air or an inert gas, and may be performed under normal pressure or reduced pressure.
[0050] The thickness of the coating film formed from the resin composition of the present invention can be selected from the range of about 0.01 μm to 10 mm depending on the application of the imidized product, and for example, when used as an adhesive layer of a semiconductor device, it can be, for example, 0.1 to 30 μm, for example, 0.2 to 20 μm, for example, 0.3 to 20 μm, for example, about 0.5 to 20 μm. When used as an adhesive layer, by adjusting the thickness to the above numerical range, it is possible to obtain an adhesive force that sufficiently guarantees the effect of maintaining adhesion with the substrate and / or lead electrode, and also to facilitate drying of the solvent and prevent the solvent from remaining in the adhesive layer as much as possible, thereby contributing to the realization of sufficient adhesiveness.
[0051] The adhesion layer of the present invention has high adhesion to metal materials and ceramics, as well as to encapsulating resin cured products, even at high temperatures, and has high durability even after exposure tests to high-temperature, high-humidity environments, i.e., an adhesion layer having a high retention rate of adhesion can be formed. In the present invention, the adhesion strength and maintenance rate of the adhesion layer of the semiconductor device were measured by the following method. The resin composition of the present invention is applied to the upper surface of a metal or ceramic substrate (40 mm x 10 mm) and heat-cured to form an adhesive layer of 10 to 25 μm. A semiconductor encapsulation resin cured product is formed on the adhesive layer by transfer molding using the semiconductor encapsulation resin composition, into a truncated cone shape with an upper diameter (Φ) of 2.90 mm, a lower diameter (Φ) of 3.57 mm, and a height of 4.00 mm. The substrate thus formed was heated at 175° C. for 6 hours, and then allowed to cool. The adhesion strength was measured on a stage heated to 175° C. and taken as adhesion strength A. The substrate thus formed was exposed to conditions of 85° C. and 85% RH for 168 hours, and then cooled. The adhesion was measured on a stage heated to 175° C., and this was taken as adhesion B. The adhesion strength is the breaking load measured by performing a shear test using a Nordson DEGA 4000 universal bond tester at a shear height of 100 μm from the upper surface of the substrate and a shear rate of 100 μm / sec. In the present invention, it is preferable that the adhesive layer has an adhesive strength A of 15 MPa or more, and an adhesive strength B of 70% of the adhesive strength A or more. In addition, although the adhesion layer of the present invention differs depending on the substrate, when the adhesion strength of an adherend in which a cured encapsulating resin is formed on the upper surface of a metal or ceramic substrate without providing an adhesion layer is taken as the adhesion strength of a blank, it is preferable that the adhesion strength A is 3.0 times or more, for example 3.7 times or more, and preferably 4.0 times or more, of the adhesion strength of the blank.
[0052] In the step of forming a cured encapsulating resin on the adhesive layer of the present invention, the encapsulating resin used and the method for forming the cured encapsulating resin are not particularly limited, and any known encapsulating resin and method for forming the cured product thereof can be used. EXAMPLES
[0053] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples. In the examples, the following devices and conditions were used for preparing samples and analyzing physical properties. (1) 1 H-NMR Equipment:BRUKER ADVANCE III-500MHz Measurement solvent: DMSO-d6 Reference material: Tetramethylsilane (TMS) (δ0.0 ppm for 1 H) (2) Gel Permeation Chromatography (GPC) Equipment: Tosoh Corporation HLC-8320GPC Column: Shodex (registered trademark) GPC KD-805 and KD-803 manufactured by Showa Denko K.K. Column temperature: 50℃ Solvent: DMF (99% by volume), THF (1% by volume), lithium bromide monohydrate (30 mmol / L), phosphoric anhydride (30 mmol / L) (3) Oven Equipment: Yamato Scientific Co., Ltd. constant temperature incubator DNF4000 (4) Nitrogen baking oven Equipment: EYELA VACUUMOVEN VOS-201SD (5) High-temperature, high-humidity oven Equipment: ESPEC Small Environmental Tester SH-262 (6) Transfer molding Equipment: AMD-5, a small transfer molding machine for hand molding, manufactured by Meiho Co., Ltd. Molding pressure: 9.8MPa Press-in time: 100 seconds Mold temperature: 175℃ (7) Bond strength test Equipment: Nordson DAGE Universal Bond Tester Series 4000 Shear height: 100 μm from the top surface of the substrate Shear rate: 100μm / sec Measurement temperature: 175℃ (8) Film thickness measurement Equipment: Kosaka Laboratory Co., Ltd. Micro shape measuring machine ET4000A Measuring force: 100μN Feed speed: 0.05mm / s (9) Infrared absorption spectrum Equipment: Thermo Scientific Nicolet iS50 FT-IR Measurement method: Total reflection measurement method (ATR method) Atmosphere: Nitrogen Temperature: room temperature
[0054] The meanings of the abbreviations of the samples used in the present invention, the preparation methods, and the means for obtaining them are shown below. CA-1: Pyromellitic anhydride [Tokyo Chemical Industry Co., Ltd.] CA-2: 4,4'-oxydiphthalic anhydride [Tokyo Chemical Industry Co., Ltd.] CA-3: 4,4'-biphthalic anhydride [Tokyo Chemical Industry Co., Ltd.] DA-1: 1,4-bis(4-aminophenoxy)benzene [Tokyo Chemical Industry Co., Ltd.] DA-2: 1,3-bis(4-aminophenoxy)benzene [TPE- from Seika Co., Ltd. R] DA-3: 1,3-bis(3-aminophenoxy)benzene [Tokyo Chemical Industry Co., Ltd.] DA-4: 4,4'-diaminodiphenyl ether [Tokyo Chemical Industry Co., Ltd.] DA-5: 1,6-bis(4-aminophenoxy)hexane [DA-6MG, manufactured by Seika Co., Ltd.]. DA-6: Synthesized by the method described in Monomer Synthesis Example 1 below was used. DA-7: Synthesized by the method described in Japanese Patent No. 6447815 was used. NMP: N-methyl-2-pyrrolidone [manufactured by Junsei Chemical Co., Ltd.] THF: Tetrahydrofuran [Junsei Chemical Co., Ltd.] DMF: N,N-dimethylformamide [Junsei Chemical Co., Ltd.] EtOAc: Ethyl acetate [Junsei Chemical Co., Ltd.] [ka]
[0055] (Synthesis Example 1 of Monomer DA-6) [ka] <Synthesis of compound [1]> 4-Nitroaniline (30 g, 0.217 mol), THF (120 g), and pyridine (19 g, 0.240 mol) were cooled to 0 °C in an ice bath and stirred. To this, a solution of acetyl chloride (19 g, 0.104 mol) in THF (10 g) was added dropwise. After completion of the dropwise addition, the temperature was raised to room temperature (25 °C) and stirred for 18 hours. After completion of the reaction, it was poured into H2O (pure water, 390 g) for dilution crystallization, filtered, and the filter cake was washed three times with methanol (130 g). The obtained crystals were dried to obtain Compound [1] (yield 40 g, 0.104 mol, yield 98%).
[0056] <Synthesis of DA-6> Under a nitrogen atmosphere, 5% Pd-C (hydrous product, 3.2 g) was added to DMF (400 g) in which Compound [1] (40 g, 0.104 mol) was dissolved, and stirred at 60 °C for 6 hours. Then, after filtration through a membrane filter to remove Pd-C, it was transferred to an autoclave and stirred at 0.4 MPa-H2 and 60 °C for 4 hours in a DMF solvent to complete the reaction. The obtained solution was filtered again through a membrane filter to remove Pd-C, and when stirred in a mixed solvent of EtOAc (400 g) / H2O (200 g), crystals precipitated (Crystal 1). This was filtered and recovered. When the filtrate was separated, crystals precipitated during the separation, so it was filtered again to recover the crystals (Crystal 2). The recovered Crystals 1 and 2 were combined and dried to obtain DA-6 (yield 14 g, 0.0429 mol, yield 41%). 1 1H-NMR (DMSO-d6, δ ppm): 9.41 (s, 2H), 7.20 (d, J = 9.0 Hz, 4H), 6.48 (d, J = 8.5 Hz, 4H), 4.80 (s, 4H), 2.23 (m, 4H), 1.60 (m, 4H).
[0057] (Synthesis Example 1) 5.81g (19.9mmol) of DA-1 and 2.77g (4.97mmol) of DA-7 were weighed out into a 300mL four-neck flask equipped with a stirrer, 104g of NMP was added, and the mixture was dissolved by stirring while feeding nitrogen. While stirring this diamine solution, 7.13g (24.2mmol) of CA-3 was added, and the mixture was stirred at room temperature for 20 hours to obtain a polyamic acid solution (PAA-1). The weight average molecular weight (Mw) of the obtained polymer was 190,000, and the dispersity (Mw (weight average molecular weight) / Mn (number average molecular weight)) was 1.9.
[0058] (Synthesis Example 2) In a 50 mL screw tube, 1.04 g (3.56 mmol) of DA-1 and 0.290 g (0.890 mmol) of DA-6 were weighed out, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.27 g (4.31 mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-2). The resulting polymer had an Mw of 150,000 and an Mw / Mn of 1.9.
[0059] (Synthesis Example 3) In a 50 mL screw tube, 1.05 g (3.59 mmol) of DA-1 and 0.270 g (0.900 mmol) of DA-5 were weighed out, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.28 g (4.35 mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-3). The resulting polymer had an Mw of 110,000 and an Mw / Mn of 1.8.
[0060] (Synthesis Example 4) In a 50 mL screw tube, 1.57 g (5.37 mmol) of DA-1 and 0.527 g (0.950 mmol) of DA-7 were weighed out, 26.1 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.80 g (6.13 mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-4). The resulting polymer had an Mw of 160,000 and an Mw / Mn of 1.8.
[0061] (Synthesis Example 5) In a 50 mL screw tube, 1.13 g (3.87 mmol) of DA-1 and 0.240 g (0.430 mmol) of DA-7 were weighed out, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.23 g (4.17 mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-5). The resulting polymer had an Mw of 160,000 and an Mw / Mn of 1.8.
[0062] (Synthesis Example 6) In a 50 mL screw tube, 1.22 g (4.18 mmol) of DA-1 and 0.122 g (0.220 mmol) of DA-7 were weighed out, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.26 g (4.27 mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-6). The resulting polymer had an Mw of 140,000 and an Mw / Mn of 1.8.
[0063] (Synthesis Example 7) 0.964g (3.30mmol) of DA-2 and 0.459g (0.820mmol) of DA-7 were weighed out into a 50mL screw tube, 17.4g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.18g (4.00mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-7). The resulting polymer had an Mw of 150,000 and an Mw / Mn of 1.9.
[0064] (Synthesis Example 8) 0.964g (3.30mmol) of DA-3 and 0.459g (0.820mmol) of DA-7 were weighed out into a 50mL screw tube, 17.4g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.18g (4.00mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-8). The resulting polymer had an Mw of 190,000 and an Mw / Mn of 2.0.
[0065] (Synthesis Example 9) 0.748 g (3.73 mmol) of DA-4 and 0.520 g (0.930 mmol) of DA-7 were weighed out into a 50 mL screw tube, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.33 g (4.53 mmol) of CA-3 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-9). The resulting polymer had an Mw of 130,000 and an Mw / Mn of 1.8.
[0066] (Synthesis Example 10) 0.941 g (3.22 mmol) of DA-1 and 0.448 g (0.800 mmol) of DA-7 were weighed out into a 50 mL screw tube, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.21 g (3.90 mmol) of CA-2 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-10). The resulting polymer had an Mw of 130,000 and an Mw / Mn of 1.8.
[0067] (Synthesis Example 11) In a 50 mL screw tube, 1.09 g (3.74 mmol) of DA-1 and 0.520 g (0.930 mmol) of DA-7 were weighed out, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 0.988 g (4.53 mmol) of CA-1 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-11). The resulting polymer had an Mw of 210,000 and an Mw / Mn of 2.0.
[0068] (Synthesis Example 12) 1.32 g (4.50 mmol) of DA-1 was weighed out into a 50 mL screw tube, 17.4 g of NMP was added, and the mixture was stirred to dissolve. While stirring this diamine solution, 1.28 g (4.37 mmol) of CA-1 was added, and the mixture was stirred at room temperature for 15 hours to obtain a polyamic acid solution (PAA-11). The resulting polymer had an Mw of 120,000 and an Mw / Mn of 1.8.
[0069] Example 1 The polyamic acid solution (PAA-1) synthesized in Synthesis Example 1 was cast onto a copper (Cu) substrate (length 40 mm x width 10 mm). This coating was heated in an oven under a nitrogen atmosphere at 110°C for 10 minutes, followed by heating at 210°C for 50 minutes, to remove the solvent and to remove the protective groups from the polyamic acid, which was then imidized to polyimide to form an adhesive layer. The thickness of the adhesive layer is shown in Table 1. On the adhesive layer formed on this substrate, an epoxy resin for semiconductor encapsulation (SUMIKON (registered trademark) EME-G720A manufactured by Sumitomo Bakelite Co., Ltd.) was molded by transfer molding into a truncated cone shape with an upper base Φ of 2.90 mm, a lower base Φ of 3.57 mm, and a height of 4.00 mm. This molded body together with the substrate was post-cured in an oven at 175° C. for 6 hours. The molded body was removed from the oven and allowed to cool, and adhesion force A was measured on a stage heated to 175° C. In addition, after the molded body was exposed to a high-temperature, high-humidity oven (85° C., 85% RH) for 168 hours (humid heat test), the molded body was removed from the oven and allowed to cool, and adhesion force B was measured on a stage heated to 175° C. The adhesion layer was evaluated by calculating the retention rate defined below from the measured adhesion A and adhesion B. Table 1 shows adhesion A, adhesion B, blank ratio, retention rate and evaluation.
[0070] Example 2 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-4. Example 3 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-5. Example 4 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-7. Example 5 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-8. Example 6 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-9. Example 7 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-10. Example 8 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-11. Example 9 A molded body was produced and evaluated in the same manner as described in Example 1, except that the substrate was a nickel-plated copper (Ni) substrate (length 40 mm x width 10 mm). Example 10 A molded body was produced and evaluated in the same manner as described in Example 1, except that the substrate was an aluminum nitride (AlN) substrate (length 40 mm×width 10 mm). Example 11 A molded body was produced and evaluated in the same manner as in Example 1, except that the coating was baked at 110° C. for 10 minutes and then at 180° C. for 50 minutes.
[0071] Comparative Example 1 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was not applied by casting. Comparative Example 2 A molded product was produced and evaluated in the same manner as in Example 9, except that the polyamic acid solution was not applied by casting. Comparative Example 3 A molded product was produced and evaluated in the same manner as described in Example 10, except that the polyamic acid solution was not applied by casting. Comparative Example 4 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-2. Comparative Example 5 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-3. Comparative Example 6 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-6. Comparative Example 7 A molded product was produced and evaluated in the same manner as in Example 1, except that the polyamic acid solution was changed to PAA-12.
[0072] The retention rate is defined as follows: Maintenance rate (%) = [Adhesion strength B after 168 hours exposure to 85°C 85% RH environment / Adhesion strength A before wet heat test] x 100
[0073] (evaluation) Those that had an adhesion A of 15 MPa or more and an adhesion retention rate of 70% or more before and after 168 hours of exposure to an 85°C, 85% RH environment were rated as A, and those that had an adhesion A of less than 15 MPa or an adhesion retention rate of less than 70% were rated as C. (Imidization rate) Infrared absorption spectrum was measured, and the first peak derived from aromatic ring (~1500 cm -1 ) and the peak due to the imide group (~1720 cm -1 A sample that was heat-treated at 110° C. for 10 minutes and at 300° C. for 50 minutes was used as the standard for an imidization rate of 100%, and the imidization rate was calculated from the relative value of the peak intensity ratio.
[0074] The blank ratio in Table 1 represents a numerical value calculated by [adhesion strength A of a molded body with an adhesive layer formed thereon / adhesion strength A of a molded body (blank) without an adhesive layer formed thereon]. In Table 1, "Cu" represents a copper substrate, "Ni" represents a nickel-plated copper substrate, and "AiN" represents an aluminum nitride substrate.
[0075] [Table 1] [Table 2]
[0076] As shown in Table 1, the molded articles of Examples 1 to 10 having an adhesion layer formed from the resin composition of the present invention exhibited a high bonding strength (adhesion A) of 15 MPa or more to a copper substrate, a nickel-plated copper substrate, an aluminum nitride substrate, and a cured product of a sealing resin, and the adhesion B after exposure to an 85°C, 85% RH environment for 168 hours showed a retention rate of 70% or more of the adhesion A. On the other hand, none of the molded articles of Comparative Examples 4 to 7 showed a bonding strength (adhesion A) of less than 15 MPa to a copper substrate or a low retention rate of 60% or less, and it was confirmed that they are unsuitable as a resin composition for forming an adhesion layer of the present invention. From these results, it is speculated that the adhesion layer formed from the resin composition of the present invention has an amino group protected by a functional group that is cleaved by heat, and an amide bond in the diamine skeleton, which causes interactions at the interfaces between the adhesion layer and the substrate and the cured encapsulant resin. Furthermore, as shown in Table 2, it was confirmed that the adhesion layer formed from the resin composition of the present invention had good adhesion performance by reaching an imidization rate of 80% or more after baking. [Industrial Applicability]
[0077] The resin composition of the present invention, which contains a polyamic acid obtained by reacting two types of diamine compounds having specific structures with a tetracarboxylic dianhydride, has a layer-forming property by thermal curing and can be widely used in the field of electronic materials such as semiconductor devices, for example, semiconductor elements, metal electrodes, and / or adhesive layers between substrates and cured encapsulating resins of semiconductor substrates, etc. In particular, it can be suitably used in next-generation power semiconductor devices in which the element temperature is high. [Explanation of symbols]
[0078] 1. Semiconductor device 2. Encapsulating resin cured product 3. Semiconductor element 4. Solder 5. Copper board 6. Ceramic board 7. Lead frame 8. Bonding wire 9. Semiconductor device adhesion layer
Claims
1. A resin composition for forming an adhesion layer for a semiconductor device, comprising: a polyamic acid obtained by reacting a diamine compound represented by the following formula (1), a diamine compound represented by the following formula (2), and a tetracarboxylic dianhydride, wherein a content of a structure derived from the diamine compound represented by formula (1) contained in the polyamic acid is 10 to 95 mol % in total, relative to a total of 100 mol % of the structures derived from the diamine compound contained in the polyamic acid; the semiconductor device adhesion layer is a primer layer at a part of the interface between the encapsulating resin cured product and the substrate and / or the lead electrode; A resin composition for forming an adhesion layer of a semiconductor device. 【Chemistry 1】 (In the formula, A 1 and A 2 each independently represents an organic acid group selected from the group consisting of a benzyloxycarbonyl group, a 9-fluorenylmethyloxycarbonyl group, an allyloxycarbonyl group, and a tert-butoxycarbonyl group; X represents a single bond or a divalent saturated hydrocarbon group having 1 to 20 carbon atoms, a divalent unsaturated hydrocarbon group having 2 to 20 carbon atoms, a divalent aromatic hydrocarbon group having 6 to 20 carbon atoms, or a divalent heterocycle; and Y represents a single bond, -O-, -CONH-, -NHCO-, -OCO-, -COO-, -NH-CO-NH-, -NHCOO-, or -OCONH-. 【Chemistry 2】 (In the formula, m is an integer from 1 to 4.)
2. A 1 and A 2 The resin composition for forming an adhesion layer for a semiconductor device according to claim 1, wherein is a tert-butoxycarbonyl group.
3. 3. The resin composition for forming an adhesion layer for a semiconductor device according to claim 1, wherein Y is -CONH-.
4. 4. The resin composition for forming an adhesion layer for a semiconductor device according to claim 1, wherein X is a divalent saturated hydrocarbon group having 1 to 18 carbon atoms, a divalent unsaturated hydrocarbon group having 2 to 18 carbon atoms, a divalent aromatic hydrocarbon group having 6 to 18 carbon atoms, or a divalent heterocycle.
5. The resin composition for forming an adhesion layer for a semiconductor device according to claim 1 , wherein the diamine compound represented by formula (1) is a diamine compound represented by the following formula (3): 【Chemistry 3】
6. The resin composition for forming an adhesion layer for a semiconductor device according to any one of claims 1 to 5, wherein the diamine compound represented by formula (2) is at least one diamine compound selected from the group consisting of diamine compounds represented by the following formulas (2a) to (2d): 【Chemistry 4】
7. The resin composition for forming an adhesion layer for a semiconductor device according to claim 1 , wherein the tetracarboxylic dianhydride is a tetracarboxylic dianhydride represented by the following formula (4): 【Chemistry 5】 (In the formula, Z represents a tetravalent organic group having 6 to 13 carbon atoms and an aromatic hydrocarbon group.)
8. The resin composition for forming an adhesion layer for a semiconductor device according to claim 7, wherein Z is selected from the group consisting of tetravalent organic groups having structures represented by the following formulas (5a) to (5k): 【Chemistry 6】 (In the formula, * represents a bond.)
9. 9. An adhesion layer for a semiconductor device, which is a cured product of the resin composition for forming an adhesion layer for a semiconductor device according to claim 1.
10. 10. The semiconductor device adhesion layer according to claim 9, wherein the imidization rate of the polyamic acid is 80% to 100%.
11. 11. The semiconductor device adhesion layer according to claim 9 or 10, wherein the adhesion strength A between the adhesion layer and the metal material, ceramic or cured sealing resin material, which is measured after heating the metal material, ceramic or cured sealing resin material provided with the adhesion layer at 175°C for 6 hours and measuring the adhesion strength A at 175°C, is 15 MPa or more, and the adhesion strength B between the adhesion layer and the metal material, ceramic or cured sealing resin material, which is measured after exposing the metal material, ceramic or cured sealing resin material provided with the adhesion layer under conditions of 85°C and 85% RH for 168 hours and measuring the adhesion strength B at 175°C, is 70% or more of the adhesion strength A.
12. A semiconductor device comprising the semiconductor device adhesion layer according to claim 9 .
13. A step of applying the resin composition for forming an adhesion layer for a semiconductor device according to any one of claims 1 to 8 to at least a part of a semiconductor element, a substrate carrying the semiconductor element, and / or a lead electrode joined to the semiconductor element to obtain a coating film; and A step of heating the coating film to form an adhesive layer. A method for manufacturing a semiconductor device comprising the steps of:
14. The method for manufacturing a semiconductor device according to claim 13, further comprising the step of forming a cured encapsulating resin on the adhesive layer after the adhesive layer is formed.
Citation Information
Patent Citations
Hair dryer
JP1986068005A
Polyimide varnish
JP1995228839A
Polyimide precursor composition, method of forming polyimide film, electronic part and liquid crystal element
JP1997302225A
Polyimide
JP2003048980A
Polyimide precursor composition, production method of polyimide precursor composition, production method of polyimide molded article, polyimide molded article, liquid crystal alignment layer, passivation film, electric wire coating material, and adhesive film
JP2015120904A